2020
DOI: 10.1186/s12913-020-05134-4
|View full text |Cite
|
Sign up to set email alerts
|

Preferences heterogeneity of health care utilization of community residents in China: a stated preference discrete choice experiment

Abstract: Background To tackle the issue with the low usage of primary healthcare service in China, it is essential to align resource distribution with the preferences of the community residents. There are few academic researches for describing residents’ perceived characteristics of healthcare services in China. This study aims to investigate the preferences of healthcare services utilization in community residents and explore the heterogeneity. The findings will be useful for the policy makers to take targeted measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…However, PHC utilization is comparatively lower than that of non-PHC institutions in China, and the doctors’ outpatient volume in higher-tier hospitals is six to ten times more than those in PHC institutions [ 7 ]. Patients’ preference for different types of medical institutions determined the PHC utilization in China [ 8 ]. Studies on the PHC preference can help optimize the PHC service delivery system, but it was far from sufficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PHC utilization is comparatively lower than that of non-PHC institutions in China, and the doctors’ outpatient volume in higher-tier hospitals is six to ten times more than those in PHC institutions [ 7 ]. Patients’ preference for different types of medical institutions determined the PHC utilization in China [ 8 ]. Studies on the PHC preference can help optimize the PHC service delivery system, but it was far from sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies about PHC preference mainly concentrated on the determinants of choosing PHC services and limited in research data. For example, characteristics of care provider, service mode, cost or cost-sharing policy, individuals' characteristics, and their experiences with PHC were the key factors impacting the preference for PHC [2,[8][9][10][11]. The provision and utilization of PHC in China varied from region to region due to large differences in socioeconomic factors and health policies [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…15 These factors were also found in studies that reviewed the access, availability, and affordability of healthcare in South Africa [15][16][17][18][19] and in other countries including Albania, China, Iran, Jordan, Nigeria, Pakistan, Spain, Tanzania, and Uganda. [20][21][22][23][24][25][26][27][28][29][30][31][32][33] A list of possible attributes to be presented to the participants was compiled, with the concurrence of the Northern Tygerberg substructure team, resulting in the finalization of the pregroup discussion list. Table 1 summarizes articles from which the attributes were retrieved, mainly from South African-related articles, thus providing a glimpse into patient preferences in the country of study.…”
Section: Selection Of Attributes List For Group Discussionmentioning
confidence: 99%
“…Some studies did not quite mirror the attributes extracted from our group discussions, possibly caused by different objectives and study methodologies. Studies in South Africa, 9 China, 21,25,26,29,30 India, 20 Iran, 27 Jordan, 33 Spain, 28 and Albania 44 included age, education, employment, travel time, transport costs, chronic illness, medication availability, illness gravity, accessibility, type of service provided, previous experience, care providers, and facilities infrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is a large body of work on stated preferences, only a few studies have been conducted regarding patients’ choice of facility, specifically within public health care. A systematic review of DCEs used to elicit patient preferences for primary healthcare showed that most studies were American or European, and focused on general practitioner (GP) consultations, [ 26 ] while Chinese studies appeared to focus primarily on the public health preferences of rural populations [ 27 , 28 , 29 , 30 ]. Only one South African DCE of public health facility preferences was identified [ 5 ].…”
Section: Introductionmentioning
confidence: 99%